Respostas
respondido por:
1
z = ax + b
z = 6 + 2i + 3mi - m
z = 6 - m + (2 + 3m)i
Isso é o que vai interessar: i(2 + 3m)
a = 6 - m ; b = (2 + 3m)
queremos a = 0
então:
6 - m = a
6 - m = 0
[ m = 6 ]
z = 6 + 2i + 3mi - m
z = 6 - m + (2 + 3m)i
Isso é o que vai interessar: i(2 + 3m)
a = 6 - m ; b = (2 + 3m)
queremos a = 0
então:
6 - m = a
6 - m = 0
[ m = 6 ]
maciellucas:
vlw
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás